Exploring the Use of Oral Corrective Feedback Among Indonesian University Students - Meidita Maharani Putri; Irma Savitri Sadikin (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study investigates the use of oral corrective feedback (OCF) in English as a Foreign Language (EFL) classrooms among Indonesian university students, with a particular focus on lecturers’ preferences and students’ perceptions. The research addresses three main aspects: the types of errors that are corrected, the strategies of OCF employed, and the timing of feedback delivery. A qualitative case study design was adopted, involving classroom observations, semi-structured interviews with lecturers, and open-ended questionnaires distributed to students. Data from these instruments were analyzed separately and then triangulated to ensure credibility and validity. The findings reveal that lecturers mainly prioritize correcting phonological and grammatical errors, as these are perceived to directly influence students’ communicative competence and overall speaking performance. Among the six OCF types proposed by Lyster and Ranta (1997), recast and repetition emerged as the most frequently used strategies. These approaches were favored by lecturers as they corrected learners subtly while minimizing the risk of embarrassment and maintaining the flow of communication. Furthermore, lecturers applied both immediate and delayed feedback depending on the classroom context and learning objectives. From the students’ perspective, OCF was generally viewed positively, as it contributed to raising awareness of errors and fostering speaking improvement. Students particularly appreciated feedback strategies that respected their confidence and speaking flow. Overall, the study underscores the importance of aligning teacher practices with student preferences to maximize the effectiveness of oral corrective feedback in EFL learning contexts.